St. Lucia : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for St. Lucia. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that the GDP growth in St. Lucia reached 3 percent in 2017, sustained by robust activity in several sectors. Favorable external conditions, coupled with hotel expansions and the addition of new flights, generated a strong recovery in tourism, with stay-over arrivals rising by 11 percent, the fastest growth in the Caribbean. Backed by strong tourism inflows, the current account balance strengthened. Unemployment declined from 21.3 percent in 2016 to 20.2 percent in 2017, but youth unemployment remains high at 38.5 percent and labor force participation has fallen. The short-term outlook is favorable, but prospects beyond that are sobering. GDP growth is expected to remain buoyant in the near term.